Remote patient monitoring based on ZigBee: lessons from a real-world deployment - Fernández-López, Helena (2014)
This work presents detailed experimental performance results, from tests executed in the hospital environment, for HM4All, a remote vital signs monitoring system based on a ZigBee body sensor network (BSN). Tests involved the use of six electrocardiogram (ECG) sensors operating in two different modes: the ECG mode involved the transmission of ECG waveform data and heart rate (HR) values to the ZigBee coordinator; whereas the HR mode included only the transmission of HR values. In the absence of hidden nodes, a nonbeacon-enabled star network comprised of sensing devices working on ECG mode kept the delivery ratio (DR) at 100%. When the network topology was changed to a 2-hop tree, the performance degraded slightly, resulting in an average DR of 98.56%. Although these performance outcomes may seem satisfactory, further investigation demonstrated that individual sensing devices went through transitory periods with low DR. Other tests have shown that ZigBee BSNs are highly susceptible to collisions due to hidden nodes. Nevertheless, these tests have also shown that these networks can achieve high reliability if the amount of traffic is kept low. Contrary to which is typically shown in scientific papers and in manufacturers’ documentation, the test outcomes presented in this paper include temporal graphs of the DR achieved by each wireless sensor device. The test procedure and the approach used to represent its outcomes, which allow the identification of undesirable transitory periods of low reliability due to contention between devices, constitute the main contribution of this work.